Nature and Composition of Ortho-Effect - Krishna Pillay, M.; Krishnan, T.S. (Asian Journal of Chemistry, 2010)
Second-order rate constants and activation parameters for the reaction of phenacyl bromide with ortho-substituted anilines were measured in methanol. The linear multiple regression analysis has been applied to the study of the effect of substituents on this reaction. The results support the conclusion of Charton that the effect of the ortho-substituents is primarily electrical. The methyl substituent behaves in an unique way.